A New Chaotic S-Box Generation Method Using Parameter Optimization of One Dimensional Chaotic Maps - Tanyildizi, Erkan; Ozkaynak, Fstih (Ieee-Inst Electrical Electronics Engineers Inc, 2019)
Chaotic systems have been used to generate the substitutional box structures. The existence of endless possibilities for the selection of the initial conditions and control parameters of the chaotic system has made it a necessity to use the optimization algorithms for generation of chaos based substitutional box structures. Most appropriate initial conditions and control parameters have been determined for four different discrete time chaotic systems using seven different optimization algorithms. A new substitutional box generation algorithm has been proposed using the optimum chaotic parameters values parameter values.
Keywords: Optimization; chaos; cryptography; random number; s-box